Swachh Bharat Abhiyan – A long journey to achieve a big dream - P. Karpaga Priya; Ashwini Katole; Gouri Kumari Padhy (Indian Journal of Community and Family Medicine, 2019)
Even after 70 years of independence, poor state of sanitation glares as one of the challenges of India. The government has tried to establish a well functioning sanitation program in the country since 1954. This program has undergone lot of changes since then and in 2014 it was renamed as Swachh Bharat Abhiyan. In order to promote safe water practices, several pipelines were installed and rivers were cleaned. Imposing Swachhta Abhiyan for carrying out activities, conducting several training programs and workshops, opening of Pink toilets, Namami Ganga, Swachh Vidyala are few of the worth mentioning initiatives under the program. Though the services are being provided at door-steps and the citizens are supported financially for toilet construction, the actual proportion of people using these toilets is under debate. Swachhata Pakhwada is being celebrated twice a year. Post celebration observance of safe disposal of waste and minimal usage of plastic is questionable. Achieving an open defecation free nation with assured safe sanitation is an initiation from the government and acceptance by the population. Implementation of these programs can only lead India becoming one of the cleanest countries in the world.